Islamic Community's Perception of Girl's Share of Inheritance in Central Lombok - Khalid, Muhammad Zaini; Nasir, Mohamad Abdun; Wathoni, Lalu Muhammad Nurul (IHSA Institute, 2025)
The purpose of this research is to study the perception of Islamic society towards the inheritance of girls in the Central Lombok Regency . This type of research is empirical law. The sample in this study tested by means of sampling. The results showed that Sasak girls who are Muslims are heirs and get a share of inheritance in the form of movable or immovable property. Before the community was familiar with Islam with the division of inheritance to girls still related to cultural customs, girls were only entitled to inheritance in the form of movable property in the form of agricultural and livestock products